Philanthropy Accountability - Edy Sukarno (Business and Entrepreneurial Review, 2007)
A causal factor of susceptibility of philanthropy in Indonesia which is now  facing turbulence era is a weak implemented accountability. Philanthropy is changing to self adjustment with the aspiration and demand of the public sectors. The changing management is needed by considering the current situation and condition, participation, and shall be supported by all of the stakeholders especially employees of not-for-profit organizations, in order to achieve the expected goal. Theprinciple of accountability requires philanthropy governance to make sure that disclosures of accurate and precise information shall be done in relation to the material consisting of financial terms and conditions, performance and leadership of the organization. The accountabilitiy is very important to prevent fraud in financial infomation and other information forwarded to not-for-profit organizations. This article is expected to provide particularly and important knowledge about the terms, functions and relationships between philanthropy accountability and information disclosures.